2011
DOI: 10.1093/jac/dkr284
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of embB mutations in multidrug-resistant Mycobacterium tuberculosis isolates in Henan, China

Abstract: ObjectivesTo determine the association between embB mutations and drug resistance, and to further investigate the mechanism of embB mutations involved in the development of ethambutol and multidrug resistance in Mycobacterium tuberculosis.MethodsOne hundred and thirty-eight multidrug-resistant clinical M. tuberculosis isolates, including 86 ethambutol-resistant and 52 ethambutol-susceptible strains, were analysed to characterize mutations within the entire coding region of the embB gene. Moreover, a two-step g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
47
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 27 publications
17
47
3
1
Order By: Relevance
“…The level of embB406 mutations among EMB-resistant isolates was rather low, whereas mutations in codon embB497 were twice as frequent [11]. In our study, no mutation at embB codons 406 and 497 was found, which may be due to the limited sample size.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The level of embB406 mutations among EMB-resistant isolates was rather low, whereas mutations in codon embB497 were twice as frequent [11]. In our study, no mutation at embB codons 406 and 497 was found, which may be due to the limited sample size.…”
Section: Discussioncontrasting
confidence: 71%
“…These genes are ubiquitous in mycobacteria and have no sequence similarity to any identified protein family in other bacteria. Consequently, the accumulation of mycolic acids due to a lack of arabinan receptors for mycolic acids results in cell death [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Ethambutol (EMB), one of the key first-line antimicrobial agents for the treatment of tuberculosis (4), plays an important role in the chemotherapy of drug-resistant TB, including MDR-TB (5). EMB inhibits arabinosyl transferases, encoded by the embCAB operon, thereby inhibiting biosynthesis of the cell well components arabinogalactan and lipoarabinomannan (6).…”
mentioning
confidence: 99%
“…Plinke et al (24) show that with regard to the frequency of mutation in different codons, 68% of the mutations are in codon 306. Dawei Shi et al (29) reported that a significant number of the mutations in codons 406 and 497 occurred in the EMBr isolates without the occurrence of mutation in codon 306. They concluded that mutation in codons 406 and 497 are the signifiers of resistance to EMB.…”
Section: Discussionmentioning
confidence: 99%